Decrease of spermatozoa with an unbalanced chromosome content after cell sorting in men carrying a structural chromosomal abnormality. (22nd May 2019) - El Fekih, S.; Tous, C.; Gueganic, N.; Brugnon, F.; Ali, H. Ben; Bujan, L.; Moinard, N.; Caire‐Tetauru, E.; Ajina, M.; Douet‐Guilbert, N.; Morel, F.; Perrin, A.
Abstract: Background: We showed that in men with a constitutional chromosomal abnormality, DNA fragmentation was significantly higher in chromosomally unbalanced spermatozoa than in spermatozoa with a normal or balanced chromosomal content. These results could be explained by a phenomenon already described in infertile men: abortive apoptosis. Objectives: To determine whether magnetic‐activated cell separation could select spermatozoa with lower levels of DNA fragmentation and unbalanced chromosome content in men carrying a structural chromosomal abnormality. Materials and methods: The spermatozoa of ten males with a chromosomal rearrangement were separated into two populations using magnetic‐activated cell separation (annexin V (−) and annexin V (+) fractions), in order to study meiotic segregation by fluorescence in situ hybridization, the percentage of spermatozoa with an externalization of phosphatidylserine by annexin V staining and DNA fragmentation by TdT‐mediated dUTP nick‐end labeling on the whole ejaculate and on selected spermatozoa in the same patient. Results: For all patients, the percentage of spermatozoa with externalization of phosphatidylserine decreased in the annexin V (−) fraction and increased in the annexin V (+) fraction as compared to the frozen‐thawed semen sample. The rates of DNA fragmentation were statistically much lower in the annexin V (−) fraction when compared to the rate before magnetic‐activated cell separation for all but one patient. Conversely, we observed a statistically significantly higher rate of DNA fragmentation in the annexin V (+) fraction for six patients. After magnetic‐activated cell separation, there was a significant increase of normal/balanced spermatozoa in the fraction of annexin V (−) for all patients. Conversely, we observed a significant decrease in the fraction of annexin V (+) for seven patients. Discussion and Conclusions: Magnetic‐activated cell separation is a promising tool for increasing the selection of healthy spermatozoa, with a decrease in the number of spermatozoa with externalization of phosphatidylserine, DNA fragmentation, and chromosome unbalance, for use in assisted reproductive technologies such as intracytoplasmic sperm injection for males with a chromosomal structural abnormality.